The Role of Accounting in Increasing Business Operational Efficiency - Rizkina, Rusdayanti; Safira, Siti Maulida; Damayanti, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Accounting is an important element in every business. Currently, businesses face increasingly complex challenges and intense competition. Therefore, operational efficiency is key in maintaining business continuity and achieving competitive advantage. This article will discuss the role of accounting in improving business operational efficiency. To dig deeper into the role of accounting in improving business operational efficiency, research can be carried out using qualitative and quantitative methods. Qualitative methods can be used by conducting in-depth interviews with accounting and business management experts. Meanwhile, quantitative methods can be used to analyze financial data from companies that have succeeded in increasing operational efficiency through the implementation of good accounting. Accounting has a very important role in improving business operational efficiency. In an increasingly complex business environment, accounting allows companies to better manage finances, measure business performance, control costs, monitor assets, and prepare accurate financial reports.